2018
DOI: 10.1080/03007995.2018.1491832
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of five systems for self-monitoring of blood glucose in the hands of adult lay-users and professionals applying ISO 15197:2013 accuracy criteria and potential insulin dosing errors

Abstract: In this study, the systems showed slight differences in the number of results within ISO 15197:2013 accuracy limits. Inaccurate SMBG measurements can result in insulin dosing errors and adversely affect glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, using only well performing devices for glucose measurement is of particular importance for clinical trials as confirmed in recently published studies. 16,17 Obviously, good device accuracy is a prerequisite to ensure patient safety. However, a suboptimal device performance may lead to other study-related problems such as potential bias in endpoints, potential inconsistencies between SMBG values and HbA1c, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…However, using only well performing devices for glucose measurement is of particular importance for clinical trials as confirmed in recently published studies. 16,17 Obviously, good device accuracy is a prerequisite to ensure patient safety. However, a suboptimal device performance may lead to other study-related problems such as potential bias in endpoints, potential inconsistencies between SMBG values and HbA1c, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…As for non-continuous glucose monitoring devices, most of them were user-friendly and rapid, but accuracy varied. In the case of glucose meters, MARD ranged from 2.3% to 21.2% 42 , 44 - 49 and FLASH from 11.2% to 22%. 23 , 29 , 30 , 50 - 52 None of the devices was equipment free.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of non-continuous monitoring devices, we grouped the devices into 6 categories: glucose meters, 42 - 49 FLASH (Abbott), 23 , 29 , 30 , 50 - 52 TensorTip Combo Glucometer (CNOGA Medical), 48 analysis software that works with a smartphone (iXensor Co), 53 GASA (Guaiacol diazo derivative, 4[(4-Hydroxy-3-methoxyphenyl) azo]-benzenesulfonic acid), 54 and Breathotron for diabetes screening, and hypoglycemia monitoring. 55 , 56 These devices measured glucose levels on capillary blood, breath, saliva and interstitial tissue (see Figure 3 and Supplemental Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some used capillary glucose monitoring devices for comparison, which themselves have accuracy issues even with the use of devices that undergo regular quality control checks. 69 Therefore, for testing accuracy, glucose levels should be checked using a reliable method, and the FDA developed clear guidance on the standards required. 70 Mean average relative difference (MARD) in glucose of a device compared with a reliable standard has been used as a simple measure to assess accuracy, although this is not without flaws.…”
Section: Differences In the Calculation Of Rate Of Change Of Glucosementioning
confidence: 99%